Utilization of the Surrounding Environment as a Source of Learning Forum for Social Sciences - Herman Herman; Rusmaniah Rusmaniah; Haris Munandar; Achmad Zainul Rozikin (The Innovation of Social Studies Journal, 2023)
The environment is a place for human growth and development including the growth and development of each child, such as patterns of social interaction, culture and customs, and habits in an area affect the growth and development of children such as instincts, habits, and acquired behavior. The surrounding environment is something that can affect students through phenomena (events, situations, or conditions) physical or social factors that affect the development of the students themselves who are located around the place where they live and can feel and see the events, circumstances or conditions around them. Utilization of environmental learning resources in IPS can be done by way of surveys, camping, field trips, project-based and scientific observing to direct exploration. The advantage gained in using environmental learning resources in IPS is that learning is more interesting and not boring for students, so that student motivation will be higher, the learning process will be more meaningful, and directly introduce the environment around the place of residence and the school environment.